2015
DOI: 10.1093/jjco/hyv141
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus S-1: a hopeful frontline treatment for Asian patients with unresectable advanced pancreatic cancer

Abstract: Objective: Gemcitabine-based chemotherapy is widely used for unresectable advanced pancreatic cancer which contains locally advanced and metastatic pancreatic cancer. We performed metaanalysis to examine whether gemcitabine plus S-1 could improve treatment efficacy as first-line chemotherapy for those patients when compared with gemcitabine alone. Methods: STATA was used to estimate the summary hazard ratios or odds ratios and their 95% confidence intervals. Heterogeneity among trials was examined by Cochran's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…All PDAC patients undergoing radical surgeries should be treated with adjuvant chemotherapy, which is vital to cure the disease and prolong survival. Gemcap is the guideline‐recommended regimen, 3,22 and GS is an alternative regimen designed for Asian patients 23–27 . As shown in Figure 1, the CHC was higher in the Gem and GS groups, which represented better chemotherapy tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…All PDAC patients undergoing radical surgeries should be treated with adjuvant chemotherapy, which is vital to cure the disease and prolong survival. Gemcap is the guideline‐recommended regimen, 3,22 and GS is an alternative regimen designed for Asian patients 23–27 . As shown in Figure 1, the CHC was higher in the Gem and GS groups, which represented better chemotherapy tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, the most common adverse event was fatigue (86%) and grade 3 events only occurred in 3% of patients. Cao et al performed a metaanalysis including 4 RCTs to examine the efficacy of GS-1, and results showed a significant OS improvement in locally advanced patients but not in metastatic patients, which suggested its disadvantage in metastatic cases (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analysis studies indicate that GEM/S-1 combination therapy, as a first-line treatment, may be more effective at increasing survival rates in patients with unresectable pancreatic cancer (5,24). Qing-Hua et al showed that GEM/S-1 combination therapy followed by oral S-1 with intensity-modulated radiotherapy (IMRT) protocol achieved a 2-year survival rate of 34.4%, which was similar to the results we have outlined in this study (2-year survival rate of 33.3%) (11).…”
Section: Discussionmentioning
confidence: 99%
“…CRT is now generally accepted as standard treatment for locally advanced pancreatic cancer (LAPC) (3,4). A combination chemotherapy using gemcitabine and fluorouracil drugs, such as S-1, is considered to be one of the more promising treatment regimens for unresectable pancreatic cancer (5,6). In contrast, the exact role of CRT in combination therapy is not well understood yet, especially when compared to monochemotherapy.…”
mentioning
confidence: 99%